The Rectum Is for Gravediggers: Homicide, HIV, Homophobia and Identity in Late Twentieth Century France - Jack D. Kiely (Tropos, 2017)
In June 2000, the French Senator Françoise Abadie defined homosexuals as ‘les fossoyeurs de l’humanité’ [‘the gravediggers of humanity’]. This definition, which came as the Senator’s reaction to the recently enacted PaCS or Civil Partnership legislation, neatly circumscribes the homophobia of the twenty-year period that had preceded it from the beginning of the HIV/AIDS crisis. Concentrating on gay men, this paper focusses on the connections between HIV/AIDSphobia and homophobia in France by focussing firstly in particular on one case of homicide in the late 1980s – that of ‘le tueur de vieilles dames’ [‘the killer of old ladies’], Thierry Paulin, who admitted to at least twenty-one killings, but whose murderous acts were imbricated indissociably by the press not only with his ‘identity’ as a homosexual, but also with his serological status – thought perhaps to have rendered him disturbed. In this period, HIV infection, homophobia and identity become intertwined with murder, be it in the literal bludgeonings of Paulin, or the fear of gays as spreaders of a deadly disease to the ‘innocent’ heterosexual population in what ACT Up-Paris call ‘le fantasme du séropositif meurtrier’ [‘the fantasy of the murderous HIV-positive person’]. More worryingly, this logic extended to isolationist and even homicidal logic against HIV sufferers around the world, leading Leo Bersani to ask in in 1987 – ‘Is the rectum a grave?’ Just over a decade later, the Pacte Civil de Solidarité (PaCS) [‘Civil Union’] debates saw similar amalgamations between HIV/AIDS and gay identity, mixed with the homicidal rage of certain of the anti-PaCS demonstrators. This time, however, in transgressing the boundaries of sexual and family norms (in requesting and defending civil partnership rights for the gay ‘community’), homosexuals in France had arguably, yet unwittingly and unintentionally, aided in provoking this murderous homophobia in a double bind, and thus to dig their own graves, rather than simply those of the ‘rest’ of humanity. Therefore, in an extension to Bersani and Abadie’s logic, this paper ultimately posits that, in modern homophobic/AIDSphobic society, the rectum is for gravediggers. To read or download this article, please follow this link: http://discovery.ucl.ac.uk/1558869 DOI: 10.14324/111.2057-2212.072